2008
DOI: 10.1002/ar.20721
|View full text |Cite
|
Sign up to set email alerts
|

Acrosome Biosynthesis in Spermatocytes and Spermatids Revealed by HPA Lectin Cytochemistry

Abstract: The origin of the acrosome is controversial, because of both its lysosomal nature and at the moment of its appearance, which seems to be species-specific. Considering the amazing organization shown by the acrosome of some urodele amphibians, HPA-colloidal gold cytochemistry was used to analyze the biogenesis of the acrosome in the urodele Pleurodeles waltl at electron microscopy level. The results showed that HPA-labeling is useful to label the acrosome and its precursor vesicles and, consequently, HPA-histoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Glycoconjugates in postmiotic cells have been reported, with an emphasis on acrosomal‐related carbohydrates (Martínez‐Menárguez et al,1992,1993; Labate and Desantis,1995; Sáez et al,1999,2004; Valbuena et al,2008). In the amphibian Pleurodeles waltl , HPA has been used as an acrosomal marker, which has allowed the analysis of the biosynthesis of the acrosome (Valbuena et al,2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycoconjugates in postmiotic cells have been reported, with an emphasis on acrosomal‐related carbohydrates (Martínez‐Menárguez et al,1992,1993; Labate and Desantis,1995; Sáez et al,1999,2004; Valbuena et al,2008). In the amphibian Pleurodeles waltl , HPA has been used as an acrosomal marker, which has allowed the analysis of the biosynthesis of the acrosome (Valbuena et al,2008).…”
Section: Discussionmentioning
confidence: 99%
“…Glycoconjugates in postmiotic cells have been reported, with an emphasis on acrosomal‐related carbohydrates (Martínez‐Menárguez et al,1992,1993; Labate and Desantis,1995; Sáez et al,1999,2004; Valbuena et al,2008). In the amphibian Pleurodeles waltl , HPA has been used as an acrosomal marker, which has allowed the analysis of the biosynthesis of the acrosome (Valbuena et al,2008). The presence of GalNAc in acrosomal carbohydrates is not exclusive to this amphibian species; it has been reported in mammals and insects (Yamamoto,1982; Lee and Damjanov,1984; Arya and Vanha‐Perttula,1984,1985,1986; Malmi and Soderstrom,1987; Malmi et al,1987,1990; Kurohmaru et al,1991,1995,1996; Ertl and Wrobel,1992; Craveiro and Bao,1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labelling in spermatocytes and spermatids could be interpreted in terms of fucosylated glycans involved in meiosis and/or spermiogenesis. If we assume that some Fuc moieties are in acrosomal glycoconjugates, this could support an explanation for spermatocyte labelling, because it has been shown that acrosome biogenesis starts in spermatocytes, before completion of meiosis, both in amphibians (Valbuena et al 2008) and mammals (Anakwe and Gerton 1990;Bermúdez et al 1994;Kohn et al 2005).…”
Section: Discussionmentioning
confidence: 94%
“…In a recent work in another amphibian, Pleurodeles waltl , we have studied the biogenesis of the acrosome by means of HPA cytochemistry, because this lectin can be used as a specific marker (Valbuena et al. ). However, in Xenopus testis, the acrosome was negative, although the rest of the spermatid was positive, as happens with WGA, s‐WGA and DSA.…”
Section: Discussionmentioning
confidence: 99%